Assessment of inhalational techniques and their common errors in bronchial asthma patients coming to tertiary hospital of South Gujarat - Shivani Dalal; Khyati Shamaliya; Anas Patni (Indian Journal of Respiratory Care, 2020)
Objective: The objective was to assess the inhalational techniques and its common errors in bronchial asthma patients. Methodology: This cross-sectional study was conducted from July 2019 to September 2019. All known asthmatic patients on inhaler therapy attending the Respiratory medicine outpatient department and who met the inclusion criteria were enrolled in the study. All participants were assessed using a pre-designed questionnaire and a standard checklist that was filled using the interview-based method. Data were entered into MS Excel 2010 and analyzed using Epi Info 7.0 and SPSS 16.0. Appropriate frequencies, percentages, and proportions were calculated, and necessary statistical tests were applied. Results: Of 113 participants, 72 (63.71%) were women and 41 (36.28%) were men. Moreover, 92 patients (81.41%) used dry powder inhalers (DPIs) and 26 patients (23%) used metered-dose inhalers (MDIs). Among these, 73 (64.60%) patients showed incorrect technique in which 57 (50.44%) patients were on DPI and 16 (14.15%) patients on MDI. Among 54 (47.78%) patients with poor clinical control, 46 (40.70%) patients with incorrect technique had partially controlled or uncontrolled asthma. Conclusion: Despite the availability of proper guidelines, incorrect inhaler technique remains the main causative factor for poor asthma control and compliance.